Food source diversity and honey production in stingless bee meliponiculture, Ogan Komering Ulu Timur, South Sumatra, Indonesia - BENI RAHMAD; NURHAYATI DAMIRI; ZAZILI HANAFIAH; DESSY ADRIANI; LAILA HANUM (Society for Indonesian Biodiversity, 2024)
Abstract. Rahmad B, Damiri N, Hanafiah Z, Adriani D, Hanum L. 2024. Food source diversity and honey production in stingless bee meliponiculture, Ogan Komering Ulu Timur, South Sumatra, Indonesia. Biodiversitas 25: 2747-2756. This research, conducted with meticulous care, aims to collect data on the diversity of food source plants and analyze vegetation, honey production, and quality in stingless bee cultivation (Meliponiculture) in East Ogan Komering Ulu District (OKUT), South Sumatra Province, Indonesia. The research was carried out using a comprehensive survey method with a qualitative and quantitative approach. The qualitative methods record the type of stingless bee food sources, while qualitative methods are used for honey quality. Direct observation, questionnaires, and in-depth interviews with beekeepers were carried out to collect data on honey production. The investigation involved observing food-supply plants in the meliponiculture area designated as the research site. Meliponiculture area location is the presence of beekeepers actively engaged in producing honey. The results of the inventory of food plant types at the meliponiculture location showed that the composition of food source plants consisted of six species of forestry plants, three species of plantation plants, seven species of MPTs, one species of crop plant, eight species of home garden and four species of shrubs. The planting pattern of plantation and forestry possesses the highest honey yield, which is 360 kg per year. Cultivated honey products have good quality and comply with Indonesian National Standards (SNI), which include organoleptic tests and laboratory tests, with results: Water content 27.14% w/w, reducing sugar content 62.05% w/w, degree of acidity 101.64 ml NaOH Kg, Total solids insoluble in water 0,066% w/w, Ash Content 0.24% w/w, and acidity degree (pH) 3.25.